Community-based HIV testing services in an urban setting in western Kenya: a programme implementation study. Issue 1 (January 2021) - Truong, Hong-Ha M; Mocello, A Rain; Ouma, David; Bushman, Dena; Kadede, Kevin; Ating'a, Eric; Obunge, Duncan; Bukusi, Elizabeth A; Odhiambo, Francesca; Cohen, Craig R
Summary: Background: Some countries are struggling to reach the UNAIDS target of 90% of all individuals with HIV knowing their HIV status, especially among men and youth. To identify individuals who are unaware of their HIV-positive status and achieve testing saturation, we implemented a hybrid HIV testing approach in an urban informal settlement in western Kenya. In this study, we aimed to describe the uptake of HIV testing and linkage to care and treatment during this programme. Methods: The Community Health Initiative involved community mapping, household census, multidisease community health campaigns, and home-based tracking in the informal settlement of Obunga in Kisumu, Kenya. 52 multidisease community health campaigns were held throughout the programme coverage area, at which HIV testing by certified testing service counsellors was one of the health services available. Individuals aged 15 years or older who were not previously identified as HIV-positive, children younger than 15 years who reported being sexually active or for whom testing was requested by a parent or guardian, and individuals who tested HIV-negative within the past 3 months but who reported a recent risk were all eligible for testing. Health and counselling services were tailored for men and youth to encourage their participation. Individuals identified during the census who did not attend a community health campaign were tracked using global positioning system data and offered home-based HIV testing services. We calculated the previously unidentified fraction, defined as the number of individuals who were newly identified as HIV-positive as a proportion of all individuals previously identified and newly identified as HIV-positive. Findings: Between Jan 11 and Aug 29, 2018, the Community Health Initiative programme reached 23 584 individuals, of whom 11 526 (48·9%) were men and boys and 5635 (23·9%) were aged 15–24 years. Of 12 769 individuals who were eligible for HIV testing, 12 407 (97·2%) accepted testing, including 3917 (31·6%) first-time testers. 101 individuals were newly identified as HIV-positive out of 1248 total individuals who were HIV-positive, representing an 8·1% previously unidentified fraction. The previously unidentified fraction was highest among men (9·8%) and among people aged 15–24 years (15·3%). Interpretation: Community-based hybrid HIV testing was successfully implemented in an urban setting. Innovative approaches that make HIV testing more accessible and acceptable, particularly to men and young people, are crucial for achieving testing and treatment saturation. Focusing on identifying individuals who are unaware of their HIV-positive status in combination with monitoring the previously unidentified fraction has the potential to achieve the UNAIDS Fast Track commitment to end AIDS by 2030. Funding: US President's Emergency Plan for AIDS Relief through the US Centers for Disease Control and Prevention.